Agricultural trade publications and the 2012 Midwestern U.S. drought: a missed opportunity for climate risk communication - Church, Sarah P.; Haigh, Tonya; Widhalm, Melissa; García de Jalón, Silvestre; Babin, Nicholas; Carlton, J. Stuart; Dunn, Michael; Fagan, Katie; Knutson, Cody L.; Prokopy, Linda S. (Elsevier, 2016)
The Midwestern United States experienced a devastating drought in 2012, leading to reduced corn and soybean yields and increased instances of pests and disease. Climate change induced weather variability and extremes are expected to increase in the future, and have and will continue to impact the agricultural sector. This study investigated how agricultural trade publications portrayed the 2012 U.S. Midwestern drought, whether climate change was associated with drought, and whether these publications laid out transformative adaptation measures farmers could undertake in order to increase their adaptive capacity for future climate uncertainty. We performed a content analysis of 1000 media reports between April 1, 2012 and March 31, 2014, sampled from ten agricultural trade publications. The results lead us to suggest that trade publications’ 2012 U.S. Midwestern drought discussion lacked information that would allow farmers and agricultural advisors to assess climate change risk and subsequent potential adaptive management strategies. Agricultural risk from climate change is very real, and farmers will need to adapt. The agricultural trade publications studied missed an opportunity to convey risk from climate change and the transformative adaptation practices necessary for a sustainable and resilient agricultural system.
Keywords: Social Amplification of Risk Framework; Risk perception; Climate change; Drought; Agriculture; Farm magazines